ANALISIS PENGGUNAAN RASIO DALAM MENGUKUR KINERJA KEUANGAN PADA PT BNI (PERSERO) TBK TAHUN 2021-2022 - Sri Wulan; Ayu Lestari Nainggolan; Septy Rindiantika; Andini Frasiska; Pandu Prasetyo (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Financial performance is a description of a company's success which can be used in decision making by analyzing financial reports using liquidity, solvency and profitability ratios with the aim of knowing and explaining the picture of financial performance at PT BNI (Persero) Tbk in each period. This research uses a descriptive method. The type of data used is secondary data. The data source used is the financial report of PT BNI (Persero) Tbk for the period 2021-2022. The data analysis used in this research is ratio calculation. The results of the analysis show the financial performance of PT. BNI (Persero) Tbk is quite good, although the results of the ROE analysis calculations fluctuate